Intelligent systems model for selective laser melting (SLM) additive modeling of the damping of Ti-6Al-4v in turbulent flow during powder bed melting in the manufacturing process - Belgada, Rihabe; Mzerd, Ahmed (Zielona Góra: Uniwersytet Zielonogórski)
With industrial modernity and its multiple advantages over global industry. The use of 3D printers has become a primary necessity for the industry. The laser melting process (SLM) is one of the most widely used processes for the manufacture of metal parts from a powder. Thanks to laser fusion manufacturing, very complex structures and geometries can be produced with very good quality. The materials used in SLM are metals that come in the form of granules. During the manufacture of the parts, the metal powder cannot be compacted as much during the process. It is therefore necessary to use supports for cantilevered structures.
Keywords: additive manufacturing; Ti-6Al-4v transport; selective laser melting; suspension of Ti-6Al-4v granules